(untitled) (Journal of Engineering, 2023)
Predicting vertical stress was indeed useful for controlling geomechanical issues since it allowed for the computation of pore pressure for the formation and the classification of fault regimes. This study provides an in-depth observation of vertical stress prediction utilizing numerous approaches using the Techlog 2015 software. Gardner’s method results in incorrect vertical stress values with a problem that this method doesn’t start from the surface and instead relies only on sound log data. Whereas the Amoco, Wendt non-acoustic, Traugott, average technique simply needed density log as input and used a straight line as the observed density, this was incorrect for vertical computing stress. The results of these methods show that extrapolated density measurement used an average for the real density. The gradient of an extrapolated method is much better in shallow depth into the vertical stress calculations. The Miller density method had an excellent fit with the real density in deep depth. It has been crucial to calculate vertical stress for the past 40 years because calculating pore pressure and geomechanical building models have employed vertical stress as input. The strongest predictor of vertical stress may have been bulk density. According to these results, the miller and extrapolated techniques may be the best two methods for determining vertical stress. Still, the gradient of an extrapolated method is much more excellent in shallow depth than the miller method. Extrapolated density approach may produce satisfactory results for vertical stress, while miller values are lower than those obtained by extrapolating. This may be due to the poor gradient of this method at shallow depths. Gardner’s approach incorrectly displays minimum values of about 4000 psi at great depths. While other methods provide numbers that are similar because these methods use constant bulk density values that start at the surface and continue to the desired depth, this is incorrect.